Clinical evaluation of adding solitary dose of magnesium to fentanyl on post-operative analgesia during combined spinal epidural technique for hip replacement procedures - Sharma, Deepak; Kaur, Daljit; Ahmad, Bilal; Kumar, Abhishek; Agarwal, Divya (International Journal of Research in Medical Sciences, 2018)
Background: Numerous receptors such as NMDA have evolved in the management of post-operative pain which can be antagonized effectively before the initiation of painful stimuli. The analgesic property of Magnesium is primarily related to the regulation of calcium inﬂux and antagonism of N-methyl-D-aspartate (NMDA) receptors distributed throughout the central nervous system. This study was designed to evaluate if addition of magnesium to epidural fentanyl as pre-emptive solitary dose could prolong post-operative analgesia during combined spinal epidural anesthesia in elective hip replacement surgeries. Methods: A total of 63 adult consented ASA grade I and II patients aged between 40 and 70 years of either sex, who met the inclusion criteria for hip replacement surgery, were randomized to receive either epidural fentanyl (Group I) or combined epidural magnesium sulphate and fentanyl (Group II). Both the groups subsequently received subarachnoid block with 0.5 % heavy bupivacaine. Intraoperative hemodynamic, subarachnoid block characteristics and 24 hours post-operative analgesia was evaluated. Results: There was significant delay in two dermatome regression for the combined fentanyl magnesium group (149.07±6.48 min) compared to fentanyl alone group (121.23±2.92 min). The post-operative VAS score was statistically lower for the combined fentanyl magnesium group (lowest:0.7±0.4 at 4th hr, highest: 2.9±0.3 at 20th hr) compared to fentanyl alone group (lowest:1.86±1.7 at 5th hr, highest: 3.37±0.9 at 4th hr). There was highly significant difference in average time to first epidural top up and 24hrs epidural top up consumption between fentanyl alone group (264.83±34.08min, 2.8±0.5) and combined fentanyl magnesium group (398±69.55min, 1.43±0.5). Total epidural top ups were 84 in fentanyl alone group and 43 in combined fentanyl magnesium group. Hemodynamic parameters were stable in both groups. Conclusions: Pre-emptive co-administration of magnesium sulphate as a solitary dose to epidural fentanyl in CSE technique prolongs the duration of post-operative analgesia, reduce the requirement of epidural top up and provide stable hemodynamic perioperatively compared to epidural fentanyl alone.